Longitudinal study of factors predicting toothbrushing less than twice daily at age 2 years in the FinnBrain Birth Cohort Study - Suokko, Hanna; Tolvanen, Minni; Virtanen, Jorma; Suominen, Auli; Karlsson, Linnea; Karlsson, Hasse; Lahti, Satu (United States, 2025)
We aimed to identify factors predicting toothbrushing less than twice daily at the age of 2 years. The data from the FinnBrain Birth Cohort Study of 506 mother-father pairs (with 506 children) were used. Logistic regression analyses were conducted of the outcome (brushing less than twice daily) at the age of 24 months. Independent variables were parental age, parental education, siblings in the household, use of childcare service, and information about whether the parents are divorced, as well as brushing of the child's teeth and the parents' own teeth at 12 months with their first order interactions. More than one quarter of the parents reported brushing their child's teeth less than twice daily at the age of 2 years. The strongest predictor for brushing the child's teeth less than twice daily at the age of 24 months was brushing child's teeth less than twice daily at the age of 12 months; the effect was significantly stronger for those children whose fathers had low education than for those whose fathers had medium/high education. Other predictors were mother's and father's own brushing at 12 months, childcare at home, and mother's low education. To improve toothbrushing in young children, early intervention is needed in families where parents brush their own teeth less than twice daily and in families with low education.